Size-independent growth of pure zinc blende GaAs nanowires - 叶显 黄辉 郭经纬 任晓敏 黄永清 王琦 (Journal of semiconductors, 2010)
Pure zinc blende GaAs nanowires were grown by metal organic chemical vapor deposition on GaAs（111） B substrates via Au catalyzed vapor-liquid-solid mechanism.We found that the grown nanowires are rod-like in shape and have a pure zinc blende structure;moreover,the growth rate is independent on its diameters.It can be concluded that, direct impingement of vapor species onto the Au-Ga droplets contributes to the growth of the nanowire;in contrast,the adatom diffusion makes little contribution.The results indicate that the droplet acts as a catalyst rather than an adatom collector,larger diameter and high supersatuation in the droplet leads to the pure zinc blende structure of the nanowire.